The relationship between emotional intelligence and employee motivation among support staff at Perbadanan Kemajuan Negeri Selangor (PKNS), Bangi./ Nor Nabilah Md Nor - Md Nor, Nor Nabilah (2017)
The purpose of the study is to identify the relationship between emotional intelligence and employee motivation among support staff at Perbadanan Kemajuan Negeri Selangor (PKNS), Bangi. The objectives of the study are to identify the level of agreement of emotional intelligence on employee motivation and to determine the relationship between emotional intelligence and employee motivation. This research used convenience sampling technique for data collection method. There are two types of analysis used in this study such as descriptive statistic and correlation analysis. Descriptive analysis looked at the four construct of Emotional Intelligence (self- awareness, self-management, social awareness, relationship management) which indicates that the employees agreed that emotional intelligence has affect employee motivation. Pearson product-moment Correlation used to measure the degree of relationship between emotional intelligence and employee motivation. The result shows a moderate positive relationship between emotional intelligence and employee motivation with significant value (p<0.01). It is further suggested that findings gleaned from this study can provide a better understanding that the role of emotional intelligence on employee motivation, which can provide researchers and practitioners with information to improve individual and organizational outcomes of interest.